Makna Diri Pengguna Rokok Elektrik Wanita di Bekasi - Faizah, Laila Nur; Mayasari, Mayasari; Rifai, Maulana (Peneliti.net, 2024)
E-cigarettes are one example of the success of the cigarette industry, which was originally only made from rolled tobacco. E-cigarette use is not only among men, but also among women. Women who smoke tend to find it more difficult to quit than men because women experience higher anxiety and mood swings. Researchers want to examine more deeply the phenomenon of female e-cigarette users in Bekasi because the city is one of the contributors to the increase in e-cigarette users in West Java. This study aims to determine the self-meaning of women who use e-cigarettes using qualitative methods and a phenomenological approach. The theory used, namely Alfred Schutz's Phenomenology Theory and G.H Mead and H. Blumer's Symbolic Interaction Theory which became the basis for researchers in conducting research. The results obtained show that each informant has a different meaning because cigarettes are attached to the informants so that they can interpret themselves as confident women who use e-cigarettes and women who are dependent on e-cigarettes. The influencing factors are the friendship environment, positive beliefs about e-cigarettes, because of the desire to relax the mind and body, and the person who always needs nicotine intake.